Study Protocol for the Evaluation of Individual Psychological Interventions for Family Caregivers of Advanced Cancer Patients - Yang, Min; Sun, Rui; Wang, Yanfeng; Xu, Haiyan; Zou, Baohua; Yang, Yanmin; Cong, Minghua; Zheng, Yadi; Yu, Lei; Ma, Fei; Qiu, Tinglin; Li, Jiang (Frontiers in Psychology, 2021)
Background: Both anxiety and depression in family caregivers (FCs) of advanced cancer patients are common, and they have a negative influence on both the FCs and the patients. Some studies suggested that a variety of interventions could alleviate the psychological symptoms of FCs. However, there is no consensus on much more effective methods for intervention, and relatively high-quality research is blank in psychological problems of these population in China. The validity of mindfulness-based stress reduction (MBSR) and psychological consultation guided by the needs assessment tool (NST) in the psychological status of caregivers will be compared in this study to select a more suitable intervention for the FCs of advanced cancer patients in China. Methods and Analysis: A randomized N-of-1 trial would be conducted at the Cancer Hospital, Chinese Academy of Medical Sciences. Fifty eligible FCs of advanced cancer patients will be recruited, and all will receive three cycles of psychological intervention treatment, with each cycle including both of MBSR and psychological consultation guided by the NST. MBSR and psychological consultation guided by the NST will be compared with each other in each cycle, and the intervention sequence will be based on the random number table generated after the informed consent has been completed. Each treatment period is 2 weeks, and the interval between different treatment cycles or treatment periods is 1 week. The self-reported scales are measured at the beginning and end of each treatment period, including the Self-Rating Anxiety Scale (SAS), the Self-Rating Depression Scale (SDS), Distress Thermometer (DT), Zarit Burden Interview (ZBI), Chinese version of the Medical Outcomes Study 12-item Short Form (C-SF-12), and Family Carer Satisfaction with Palliative Care scale (FAMCARE-2). Dissemination: The protocol of the study was approved by the Institutional Review Board of the Ethical Committee of the Cancer Hospital, Chinese Academic of Medical Science. The results will be published in a peer-reviewed medical journal. The study is registered at Chinese Clinical Trials Registry with the trial registration number chiCTR2000033707. This study employs an innovative methodological approach on the effectiveness of MBSR and psychological consultation guided by the NST for psychological status of FCs of advanced cancer patients. The findings of the study will be helpful to provide high-quality evidence-based medical data for psychological intervention of FCs of advanced cancer patients, and guide clinicians on best quality treatment recommendations.